Multiple small bowel gastrointestinal stromal tumors presenting as acute abdomen: A rare case report - Kumar, B Sunil; Reddy, Gayathri; Ahmed, Syed Arbaaz; Goud, M Vijay Kumar (Indian Journal of Case Reports, 2026)
Gastrointestinal stromal tumors (GISTs) are rare malignant mesenchymal neoplasms of the alimentary tract that account for a small proportion of gastrointestinal tumors and most commonly arise from the stomach and proximal small intestine. Multiple synchronous jejunal and ileal GISTs are exceedingly uncommon, and presentation with acute abdomen due to complications such as perforation and intussusception is particularly rare. A 55-year-old male presented with an acute onset of severe abdominal pain, bilious vomiting, and constipation. Clinical evaluation and imaging were suggestive of acute intestinal obstruction secondary to a mid-jejunal mass. Emergency laparotomy revealed multiple small bowel tumors involving the jejunum and ileum, including a 10 × 8 cm jejunal mass with anti-mesenteric perforation with densely adherent omentum and a 4 × 3 cm mid-ileal mass serving as a lead point for intussusception. Histopathological examination of the resected specimens showed a tumor arising from the muscularis propria composed of atypical round to spindle cells arranged in fascicles, bundles, and sheets, with areas of atypical mitoses, necrosis, and tumor emboli, features consistent with high-grade GIST. The postoperative period was complicated by refractory septic shock, and the patient unfortunately succumbed on postoperative day 2 despite intensive care. This case emphasizes the importance of considering GISTs in the differential diagnosis of small bowel masses presenting with acute intestinal obstruction and highlights the potential for aggressive clinical behavior and poor outcome in large, high-grade tumors complicated by perforation.